The Challenges of Stakeholder Collaboration in Conservation Programs at Way Kambas National Park - Irmayanti Irmayanti; Ani Agus Puspawati (Eastasouth Institute, 2026)
Collaborative governance has become a central approach in addressing complex conservation challenges that exceed the capacity of single actors. This study examines stakeholder collaboration in conservation programs at Way Kambas National Park, Indonesia, with a focus on identifying the key challenges that affect the sustainability of collaborative arrangements. The research adopts a qualitative case study approach, drawing on in-depth interviews, document analysis, and field observations involving government authorities, conservation organizations, and buffer-zone communities. The findings reveal that collaboration operates adaptively but remains constrained by several interrelated challenges, including rigid administrative procedures, dependence on external funding, socio-economic pressures affecting community participation, and the fragility of trust due to inconsistent communication and staff turnover. These challenges demonstrate that effective conservation collaboration requires more than formal partnerships; it depends on institutional flexibility, stable resource support, sustained community benefits, and continuous trust-building among actors. The study concludes that strengthening collaborative governance in conservation areas necessitates adaptive institutional mechanisms and long-term social and financial strategies to ensure enduring conservation outcomes.